Treatment decisions of patients with Class II Division 2 malocclusion and severe tooth wear: a systematic review - Yuhan Ma; Weijia Zhao; Sisi Zhang; Xiaoting Jin; Jianhao Xu; Baiping Fu; Ying Shi (Nature Publishing Group, 2024)
Abstract Background The treatment strategy for patients with severe tooth wear associated with Class II Division 2 malocclusion remains a major challenge for dental practitioners. Objectives To systematically review and summarize the literature on treatment strategies, restoration procedures and clinical outcomes for Class II Division 2 malocclusion patients with severe tooth wear. Methods A literature review was conducted using Pubmed, Embase, the Cochrane Library, and Web of Science to identify eligible articles. Publications until October 16th, 2023 were searched independently and cross-checked by two researchers. Results Of 1513 articles screened, 10 reports detailed treatment processes, including six males and four females aged 34-68 years old. Four articles recorded pre-treatment freeway space (FWS) values ranging from 5 to 9 mm. All ten cases had significant occlusal vertical dimension (OVD) loss and the increase in OVD after treatment ranged from 1 to 7 mm. Pre-prosthetic orthodontic treatment was performed in two cases, in one of which only the maxillary region was orthodontically treated. The most common restorations provided were full coverage restorations. In most cases, temporary restorations were applied before the permanent restorations for eight weeks to six months. Four different sequences of final restoration were proposed. Follow-up ranged from four months to six years and included seven patients, one of them showed symptoms of temporomandibular disorder (TMD). Conclusions A multidisciplinary team (MDT) approach to treatment is recommended. Consideration of pre-prosthetic orthodontic treatment is essential. Commonly used cephalometric measurements for anterior teeth include the interincisal angle and collum angle. The increases in OVD ranging from 1 to 7 mm can be effectively accommodated. Temporary restorations are recommended to accommodate the OVD, and the transition periods of 8 weeks to 6 months help the patients adapted well. Four different sequences for final rehabilitation have demonstrated positive clinical outcomes. Full crown restorations have emerged as the preferred choice for the ultimate restoration of these patients.